Looking race in the face. (February 2017) - Mitchell, Derek; Hinueber, Jesse; Edwards, Brian
Schools that achieve strong results for black students address racial dynamics directly, empower students to bring their whole selves to school, and teach in ways that leverage students' experiences and cultures. These schools do four things to ensure success with their black students: They direct attention, strategies, and resources to black student achievement; they provide opportunities for adult learning about race, culture, class, and power; they foster strong relationships between educators and black students; and they create classroom environments that emphasize excellence and empower students to exercise agency over their own learning .